Research on softening curve of recycled concrete using base force element method in meso-level. Issue 7 (12th August 2019) - Peng, Yijiang; Chen, Xiyun; Ying, Liping; Kamel, Mahmoud M.A.
Abstract : Purpose: Based on the base force element method, a two-dimensional random circle aggregate model with Monte Carlo principle is proposed to carry out research on softening curve in meso-level. Design/methodology/approach: The meso-level structure of recycled concrete is considered as the five-phase materials composed of aggregate, old interfacial transition zone, old mortar, new interfacial transition zone and new mortar. A multi-polyline damage model is adopted to describe the nonlinear mechanical behavior of recycled concrete material. The destruction state of the element is determined by the first strength theory. The research studies on damage process of recycled concrete under the loading conditions of uniaxial tension were established using the base force element method. Findings: The softening curves of recycled concrete are obtained, which are in good agreement with experiment results. Simulation results show that the macroscopic mechanical properties and failure mechanism can analyze more reasonably from mesoscopic structure. Besides that, it can be investigated from the numerical results of the size effect in recycled concrete through the mesoscopic heterogeneity. Furthermore, the form of aggregate distribution has influence on the crack path but little effect on the tensile strength of recycled concrete. Originality/value: The results show that the base force element method has been successfully applied to the study of softening curve of recycled concrete under uniaxial tension.